Implementasi Data Mining pada Penjualan Kopi Menggunakan Algoritma Apriori - Irma Rosmayati; Wahyuningsih Wahyuningsih; Eliya Fatma Harahap; Hani Siti Hanifah (Institut Teknologi Garut, 2023)
Coffee shops are currently in great demand by the public, especially teenagers because of the many types of coffee and attractive presentation. Due to the large number of coffee sales, more and more data has accumulated. To minimize unused data, the data is processed using data mining with an a priori algorithm approach. This a priori algorithm aims to make recommendations to the coffee shop to make discounts and recommendations to prospective buyers to buy products that are often purchased by the public. The dataset used is sales data for November 2022. The application of data mining to sales of coffee with the highest rule appears on Kopsu Friends and V60 with a support value of 25% and a confidence of 83%.